(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
We intend to provide elements of analysis about the processes of territorialization connected to the construction of memories about the celebration of the Day of the Dead in the case of Quechua migrants from the Cochabamba region of Bolivia (Punata and Cuchu Punata). We focus on comprehending the processes of memory, forgetting, and silence –within the context of subor- dination and mobility– amongst migrants. The study analyzed takes place in the city of Caleta Olivia, an urban center and oil hub in the northern province of Santa Cruz, Argentina. We are interested in analyzing the complex ways in which the indigenous and migrant affiliations of these individuals intersect in an urban territorial context that differs from the rural environment of Cochabamba. Additionally, we are interested in the way a religious territory is constructed with connections not only to the place of origin and the recipient country, but also, more importantly, to the territoriality that this group from Cochabamba gives new significance through their religious practices around death.